Mencermati Kepemimpianan Komprehensif dalam Asthabrata - Pardi Suratno (Universitas Sebelas Maret, 2022)
The concept of leadership is found in many Javanese old texts, such as Serat Asthabrata, Serat Wulangreh, and Serat Tripama. Among these old texts, the concept of leadership written in Asthabrata is regarded as the most popular one in the life of Javanese or Indonesian people. It is because the development of the leadership concept in Asthabrata was unique and interesting. Asthabrata’s teachings were born in the Hinduism era and derived from Serat Ramayana. Following the Javanese society’s belief that changed from Hinduism to Islam, the leadership concept of Asthabrata shifted. The Hinduism concept symbolized in Hindu Gods’ roles turned symbolically into natural objects. It occurred because Islamic beliefs did not adhere to Hindu Gods; therefore, the concept was realized symbolically in natural objects, such as the sun, earth, moon, fire, ocean, star, wind, and cloud. One of the intriguing things to understand is that any of those objects provide no leadership. However, leadership is comprehensive - an ideal leader is the one who meets the characteristics of those objects, known as woluning atunggal (eight as unity). This article aims to describe the characteristics of comprehensive leadership in Asthabrata teachings as a reference to develop the ideal leadership concept in Indonesia.